Aircraft maintenance checks using critical chain project path - Kulkarni, A.; Yadav, D.; Nikraz, Hamid (2017)
Purpose – Aircraft operators incur significant costs when an aircraft is taken out of service for maintenance. The purpose of this paper is to present a method for reducing time duration of aircraft maintenance checks using critical chain project management (CCPM) principle. Design/methodology/approach – A case study of a typical heavy maintenance check performed on an Airbus 320 aircraft is undertaken for the analysis. The critical chain method is applied to develop a plan with a reduced duration and a survey and field observations to validate the findings have also been carried out as a part of this paper. Findings – The paper compares the traditional project management method with CCPM in view of reducing the aircraft down time duration for maintenance. This paper repositions buffers and other techniques to shorten the chain path and a reduction in the total duration of the project by five days is achieved. Research limitations/implications – It is argued that the application of CCPM principle can reduce the duration of an aircraft maintenance check, but this paper is done in a single project situation focusing on project planning and execution. Therefore, additional study may be required to examine other issues. Originality/value – Cost of the maintenance is second highest expenditure factor for an airline operator. Therefore, it is necessary to drive the maintenance cost down. The paper demonstrates that the duration of a maintenance check can be reduced by 8.9 per cent using the method suggested in this paper.